THE OCCURRENCE OF THE MIRATIVITY WITHIN VARIOUS SENTENCE TYPES IN UZBEK AND ENGLISH LANGUAGE (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This research investigates the expression of mirativity in various sentence structures in Uzbek and English, with particular emphasis on the structural and pragmatic encoding of unexpected events, speaker astonishment, and the disclosure of new information in both languages. The study further examines how the category of mirativity manifests across different sentence structures in English and Uzbek, including declarative statements, rhetorical questions, exclamatory phrases, and cases of inversion.